An energy‐frequency parameter for earthquake ground motion intensity measure. (17th October 2022) - Chen, Guan; Yang, Jiashu; Liu, Yong; Kitahara, Takeshi; Beer, Michael
Abstract: A novel scalar ground motion intensity measure (IM), termed the energy‐frequency parameter, is proposed based on the Hilbert‐Huang transform. To validate the effectiveness of the proposed IM, the correlation analysis between the engineering demand parameter (EDP) and energy‐frequency parameter is performed using 1992 recorded ground motions, in which EDP is the maximum inter‐storey drift of structures obtained by nonlinear time‐history analysis. Results show that the energy‐frequency parameter has a strong linear correlation with EDP at natural logarithm, and this correlation is applicable for various structural fundamental periods. We also verified that the lognormal cumulative distribution function can characterize the energy‐frequency parameter‐based fragility function, which can further facilitate the application of the parameter in seismic risk analysis. Besides, the strong correlation between the energy‐frequency parameter and other IMs (such as PGA, PGV, PGD, CAV, I a I_a, v r m s v_rms, and SI) potentially makes the proposed IM widely applicable in seismic risk analysis. Moreover, since the energy‐frequency parameter depends only on the frequency‐domain characteristics of the ground‐motion signal, it may closely link to seismological theory and provide new insights into seismology engineering.